2016
DOI: 10.1111/pde.12981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing in Dermatology: A Survey Analyzing Obstacles to Appropriate Care

Abstract: The role of genetic testing in the practice of dermatology is expanding, yet obtaining coverage for genetic testing remains a challenge. We propose several solutions as to how this can be remedied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Providers such as neurologists, psychiatrists, pulmonologists, dermatologists, and cardiologists were involved in ordering genetic testing, and the frequency and comfort level varied by setting. [115][116][117][118][119][120] In studies that assessed referral patterns, between 9% and 58% of nongenetics HCPs reported that they had never referred a patient to a clinical genetics service for consultation. 91,116,117,121 In these studies, neurologists and psychiatrists both had lower referral rates to genetics, but neurologists were more likely than psychiatrists to have ordered genetic testing.…”
Section: Case Loadsmentioning
confidence: 99%
“…Providers such as neurologists, psychiatrists, pulmonologists, dermatologists, and cardiologists were involved in ordering genetic testing, and the frequency and comfort level varied by setting. [115][116][117][118][119][120] In studies that assessed referral patterns, between 9% and 58% of nongenetics HCPs reported that they had never referred a patient to a clinical genetics service for consultation. 91,116,117,121 In these studies, neurologists and psychiatrists both had lower referral rates to genetics, but neurologists were more likely than psychiatrists to have ordered genetic testing.…”
Section: Case Loadsmentioning
confidence: 99%
“…Pediatric patients with genetic skin disorders may first present to a dermatologist due to physical symptoms. Shagalov et al illustrated that nearly all practicing pediatric dermatologists care for patients requiring genetic analysis, but that due to poor rates of insurance coverage, the number of patients completing testing is quite low (Shagalov, Ferzli, Wildman, & Glick, 2017). Additionally, practicing dermatologists in the community may not regularly see patients with these rare syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Shagalov et al report the results of a survey that examined obstacles to obtaining genetic testing for patients with genetic skin diseases. Respondents were pediatric dermatologists in the United States, the majority of whom were working in academic centers.…”
mentioning
confidence: 99%
“…Genetic testing usually (but not always) provides parents with a definitive pattern of inheritance and the likelihood of transmission of the disease (e.g., autosomal dominant or recessive, sex linked, mitochondrial or mosaic inheritance) and allows for effective genetic counseling. Shagalov et al reported that 25% of participants in their survey cited prenatal diagnosis as a reason to obtain genetic testing. Historically, prenatal diagnoses for suspected genodermatoses were made using chorionic villous sampling or fetal skin biopsy .…”
mentioning
confidence: 99%
See 1 more Smart Citation